Virtual literary gathering as a strategy to improve school coexistence - Martinez-Ubillús, Gely Coraly (2021)
Objective. The main objective of this study is to design a virtual literary gathering strategy to improve school coexistence at the Mallaritos Educational Institution, responding to a problem of the population under study. Methods. A non-experimental design was used for this research, which was applied in a cross-sectional manner. A questionnaire with 22 items divided into four dimensions was also applied: interpersonal relationships, democratic discipline, relationship with the context and cyberbehavior, applied to a sample of 43 students in the fourth grade of high school. The validity of the instruments was assessed under three aspects: criterion validity, construct validity and content validity determined through the judgment of experts. These experts rated the pertinence and relevance of the instrument. Reliability was measured through Cronbach's and McDonald's test, where 0.952 was obtained in both results. Results. The findings were unfavorable in terms of the variable under study, the low and medium levels of 30% and 42%, respectively, were obtained, which is why the proposed objective. Conclusions. It is concluded that it is necessary to apply a virtual literary gathering strategy that allows the improvement of school coexistence in this institution because it is necessary for learning in a collaborative environment.